Prevalence and Correlates of Illicit Substance Use Among Young Adults Experiencing Homelessness in Seven Cities Across the United States - Chassman, Stephanie (Journal of drug issues, 2022)
BackgroundYoung adults experiencing homelessness (YAEH) engage in substantially higher substance use rates than housed young adults. This current study builds on previous research by investigating the prevalence of and salient correlates of illicit substance use across a seven-city sample.MethodsThis study used the Homeless Youth Risk and Resiliency Survey (HYRRS) dataset, n=1426 Young adults experiencing homelessness to study patterns and correlates of illicit substance use.ResultsMultivariate logistic regression analyses were used to assess correlates of substance use. Study site, age, gender identity, sexual orientation, history of suicidal ideation, use of specific substances, and trading sex for drugs were associated with five types of illicit substance use (ecstasy, cocaine, crack, methamphetamine, and injection drug use).ConclusionFindings indicate that substance use interventions for YAEH must be multifaceted, addressing illicit and multiple substance use, along with the myriad factors associated with substance use among this at-risk group.